Uji Antagonis Cendawan Patogen Ikutan Benih Pometia pinnata, Pterocarpus indicus, Aquilaria filaria dengan Bakteri Proteus penneri dan Enterobacter hormaechei - Nunang L. May; Tommy Wenno; Evelin A. Tanur (Universitas Musamus, Merauke, Papua, 2015)
The use of microbial antagonists is one alternative to reduce the rate of a population of pathogenic fungi. This study aims to determine the ability of an antagonist of the bacteria Proteus penneri and Enterobacter hormaechei isolated from spores Endomikoriza types Glomus sp. with fungal pathogens. The research object is a pathogenic fungus that comes from the seed Pometia pinnata, Pterocarpus indicus and Aquilaria filaria. Test antagonists using Varese et al (1996) by observing the inhibition of bacterial to fungal pathogens tested. The results showed that the percent inhibition of bacteria against fungi P. penneri follow Pometia pinnata seed of 56.11%, Pterocarpus indicus 28.70% and 30.56% Aquilaria filaria. Testing bacteria E. hormaechei generating percent inhibition of fungus P. pinnata seed followup of 18.56%, P. indicus 46.85% and A. filaria 32.41%. Inhibition of pathogenic bacteria in the fungus P. penneri ultimate origin of P. pinnata seed and the lowest in P. indicus. Whereas inhibition of pathogenic bacteria E. hormaechei highest on fungal origin P. indicus and lowest seed in P.pinnata.